Implementation of the Mu'adallah Education System at Musthafawiyah Purba Baru Islamic Boarding School, Mandailing Natal Regency - Ramayani, Nurmisda; Luqman, Ahmad Sanusi; Sudarmayani, Sudarmayani (LPPPI Publishing, 2025)
This research is motivated by the development of Islamic boarding schools which initially only studied religious sciences, but the ever-changing times in all aspects of life are the main challenge for Islamic boarding schools in maintaining their existence. This study aims to determine the implementation of the mu'is education system in the Musthafawiyah Purba Baru Islamic boarding school in Mandailing Natal Regency. This type of research is a qualitative approach. The results of this study indicate that: 1) Planning the implementation of the mua'is education system at Musthafawiyah Purba Baru Islamic Boarding School begins with affirming and strengthening the vision, mission, goals and curriculum. There are educational units that compile curriculum structures by following the full standard of the government curriculum, namely the Ministry of Religion curriculum and the Ministry of Education and Culture curriculum. The curriculum structure of the Musthafawiyah Purba Baru Islamic boarding school includes religious and general subjects with a composition of 70% and 30%; 2) The implementation of the implementation of the mua'is education system at Musthafawiyah Purba Baru Islamic Boarding School is basically the material used based on the books related to aqidah, morals and shari'ah and to support the learning process students are equipped with linguistic and general sciences. In learning activities carried out include teaching materials/contents, approaches, learning methods, and assessments; and 3) The implementation of the evaluation of the Musthafawiyah Purba Baru Islamic boarding school uses criteria or assessment standards determined by the pesantren and their respective teachers by means of local Imtihan consisting of imtihan shafahi (oral) and imtihan tahriri (written). Then, related to the provision of diplomas or graduation marks, Pesantren Musthafawiyah Purba Baru states that even though santri have passed the final exam, they cannot get a diploma before serving for 1 year.